Kajian Penggunaan Sistem Informasi Customer Service dengan Technology Acceptance Model (Studi Kasus Pada PT. SMARTFREN Semarang) - Johan Kemal Sahala Martua; Selo (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2013)
PT. Smartfren Telecom, Tbk. is a provider of telecommunications services based on CDMA technology that is the largest licensed cellular and limited mobility (fixed wireless access), and has network coverage CDMA EV-DO (equivalent broadband mobile network with 3G) in Indonesia. Smartfren also the first telecom operator in the world that provides CDMA EV-DO Rev. B (equivalent to 3.5 G with download speeds up to 14.7 Mbps) and the first CDMA operators providing Blackberry services. This research covers what are the factors that influence the use of information systems to identify the level of customer service and customer service information system acceptance in the telecommunications industry. Factors affecting the public who had used the customer service information system PT. Smartfren Semarang is a benefit to using the customer service information system, the ease in using the customer service information system, the purposes in the customer service information system usage, frequency of use of customer information service system, the interest to use the customer information system service, and the rates in accordance with the benefits received in the customer service information system.